An efficient low-temperature route to nitrogen-doping and activation of mesoporous carbons for CO2 capture. Issue 97 (13th October 2015) - Huang, Kuan; Chai, Song-Hai; Mayes, Richard T.; Veith, Gabriel M.; Browning, Katie L.; Sakwa-Novak, Miles A.; Potter, Matthew E.; Jones, Christopher W.; Wu, You-Ting; Dai, Sheng
Abstract : Nitrogen-doping of soft-templated mesoporous carbons is achieved at low temperatures (230–380 °C) and high yields (>90%) by using sodium amide. Abstract : An innovative strategy for post-synthesis nitrogen-doping of mesoporous carbons (MCs) with high yields (>90%) at low temperatures (230–380 °C) by using a strong base, sodium amide (NaNH2 ), was developed. The as-prepared N-doped MCs exhibit a significantly enhanced CO2 adsorption performance in terms of capacity and selectivity when compared to their parent MCs.